MINAT DAN MOTIVASI MAHASISWA DALAM MENGIKUTI PERKULIAHAN DENGAN SISTEM E-LEARNING PADA JURUSAN MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH PALOPO - Denada Adramadani; Adil .; Ahmad Suardi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze students' interest and motivation in attending lectures with the e-learning system. Sampling research using accidental sampling method with a total of 100 respondents. Data were analyzed using a quantitative approach through Multiple Regression Analysis using the SPSS Application. The results of this study indicate that Fcount is 225,445 at a significance level of 5% and Ftable is 2.70 at a significance level of 5%. Thus, Fcount (225.445) > Ftable (2.70), which means that simultaneously interest and motivation affect lectures on the e-learning system. The e-learning system is 82.3% influenced by interest and motivation and the remaining 17.7% is influenced by other factors not examined or outside the research model. Partially interest has a positive and significant effect on e-learning system lectures. Partially, motivation has a positive and significant effect on e-learning system lectures.